2023
DOI: 10.1186/s13613-023-01157-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender and racial differences in first and senior authorship of high-impact critical care randomized controlled trial studies from 2000 to 2022

Subhash Chander,
Sindhu Luhana,
Fnu Sadarat
et al.

Abstract: Background Females and ethnic minorities are underrepresented in the first and senior authorships positions of academic publications. This stems from various structural and systemic inequalities and discrimination in the journal peer-review process, as well as educational, institutional, and organizational cultures. Methods A retrospective bibliometric study design was used to investigate the representation of gender and racial/ethnic groups in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Compared to nephrology, cardiovascular, and gastroenterology-related clinical trials, females were better represented in the first and last authorship positions of clinical trials related to other subspecialties. Among critical care, clinical trials published between 1981 and 2020, 11.8% of the first authors were females [45], while the proportion was 24.6% and 16.6% in the first and last authorship positions among clinical trials published between 2000 and 2022 [46]. Similarly, the proportions of females in the first and last authorship positions were 27.7% and 14.9% among neurovascular clinical trials (2000-2021) [47], 33.3% and 26.4% in rheumatology (2015-2019) [48], 28.4% and 16.8% in sports medicine (2000-2020) [49], 46.6% and 33.4% in exercise/rehabilitation (2014-2022) [50], and 36.2% and 26.9% in dermatology (2010-2020) [51] subdisciplines.…”
Section: Representation Of Female Authors In Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to nephrology, cardiovascular, and gastroenterology-related clinical trials, females were better represented in the first and last authorship positions of clinical trials related to other subspecialties. Among critical care, clinical trials published between 1981 and 2020, 11.8% of the first authors were females [45], while the proportion was 24.6% and 16.6% in the first and last authorship positions among clinical trials published between 2000 and 2022 [46]. Similarly, the proportions of females in the first and last authorship positions were 27.7% and 14.9% among neurovascular clinical trials (2000-2021) [47], 33.3% and 26.4% in rheumatology (2015-2019) [48], 28.4% and 16.8% in sports medicine (2000-2020) [49], 46.6% and 33.4% in exercise/rehabilitation (2014-2022) [50], and 36.2% and 26.9% in dermatology (2010-2020) [51] subdisciplines.…”
Section: Representation Of Female Authors In Clinical Trialsmentioning
confidence: 99%
“…Of the included studies, one reported authorship trends in both clinical trials and clinical practice guidelines [39], while more than 15 studies exclusively reported authorship trends in clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53] and 14 reported authorship trends in clinical practice guidelines [54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The inclusion of women in nephrology research is a critical step but does not single-handedly resolve the deep-seated issues of gender and racial biases in medical research. Historically, clinical research has disproportionately centered on male participants, which has led to significant gaps in the collective understanding of different manifestations of diseases as they affect women, particularly women of color [ 5 , 6 ]. This discrepancy hampers the development of diagnostic tools, treatment plans, and clinical guidelines that accurately reflect the health needs of all women.…”
Section: Editorialmentioning
confidence: 99%
“…Patient education and empowerment are indeed pivotal in promoting an equitable healthcare landscape, particularly within nephrology [ 4 , 13 ]. This is especially true for women and women of color, who have historically been underrepresented in patient advocacy and decision-making roles [ 6 ]. Ensuring that women have the knowledge and the power to actively participate in their healthcare decisions is crucial.…”
Section: Editorialmentioning
confidence: 99%
“…However, female representation in these areas is much lower than expected based on the female ICM specialist workforce ( 1 ), suggesting that proportionality does not account for this observation alone. Male physicians consistently outnumber their female counterparts both as faculty members at conferences ( 5 ) and as first or last authors of scientific articles ( 6 ). The COVID-19 pandemic has disproportionately affected the productivity and scientific output of female academics, leading to the loss of female scientific expertise from the public realm ( 7 ) and a widening of the gender gap in critical care medicine.…”
mentioning
confidence: 99%